Cryopreservation of sperm in farmed blacklip abalone (Haliotis rubra Leach, 1814). (7th March 2014) - Liu, Yibing; Xu, Tong; Robinson, Nicholas; Qin, Jianguang; Li, Xiaoxu
Abstract This study developed a technique of sperm cryopreservation using liquid nitrogen (LN) vapour in farmed blacklip abalone Haliotis rubra through evaluating the following five key factors: (1) cryoprotectant agent (CPA) toxicity; (2) cooling temperature; (3) thawing temperature; (4) sperm to egg ratio and (5) sugar addition, using sperm motility or fertilization rate as quality assessment indicators. The results demonstrated that 6% dimethyl sulfoxide (DMSO) was the best single CPA for sperm cryopreservation in this species. The highest post‐thaw sperm motility was achieved when sperm were exposed to LN vapour for 10 min at 5.2 cm above the LN surface and thawed at 60°C and recovered at 16°C in seawater baths. Post‐thaw sperm motility was found to be significantly higher when 6% DMSO was used in combination with 1% or 2% glucose than 6% DMSO alone. Further evaluation of fertilization rate between these CPAs showed that 6% DMSO+2% glucose achieved the highest fertilization rate of 70% at a sperm to egg ratio of 10 000:1.